Palette 08 Iridescent : Holographics in design. - Cheung, Victor (Hong Kong : viction:ary, 2018)
101 ; Alexia ROUX ; Jamet, Alexis ; Rainaud, Alycia ; Reiter, Amanda ; Anagrama ; Kulachek, Anna ; Tzimas, Aron ; Hählen, Balmer ; BLOW ; bonjour garçon studio ; Bruce Mau Design ; Build ; Blanchette, Caroline ; Chiii Design ; COLLINS ; Barkle, Daniel ; Dasha F ; Evans, Davy ; Dawn Creative ; Design Ranch ; dn&co. ; ECAL / University of Art and Design Lausanne ; Established ; Tison, Evin ; Folv Creative Agency ; Foreign Policy Design Group ; Fundamental ; Futura ; Glas Italia ; Thorkels, Greta ; HATTERN, UMZIKIM ; Hey ; HOUTH ; Hovercraft Studio ; Irradié ; Kati Forner Design ; Kimgarden ; Kolory ; Chulwoong, Lee ; Wysocki, Marcin ; Iriberri, Mariana Cecilia ; Lewandowska, Marina ; Tremblay, Martin ; Witczak, Mateusz ; Thorsby, Michael ; Midnight Design ; Mubien ; nendo ; Nonverbal Club ; Not Available Design ; Noviki ; Packvision ; Paperlux Studio ; Paraámetro Studio ; Friedlander, Paul ; Pentagram ; PONYO PORCO ; PRYSME ; Pyramid ; Volk, Radmir ; Khasanov, Ruslan ; Yoon, Saerom ; selgascano ; Gerber, Selina ; Semiotik Design Agency ; Shuka Design ; Sion Hsu Graphic ; Studio AH-HA ; Studio Band ; Studio My Name is Wendy ; Studio South ; Sie, Sydney ; Tissot, Thibaud ; thonik ; Chia-hao, Tsai ; Shu-yu, Tsai ; twomuch ; Golubovic, Vanja
boek